Tradução e adaptação transcultural da versão brasileira do caries impacts and experiences Questionnaire for Children (B- caries-QC) - Juliana Freire Maia Miranda (2022)
Children and adolescents may be affected by several oral problems. Measures to assess oral health-related quality of life (OHRQOL) have been developed by means of scales that measure the impact of these oral problems on people's quality of life. The Caries Impacts and Experiences Questionnaire for Children (CARIES-QC) was developed as a dental caries-specific quality of life measure that involves children and adolescents at all stages of their development and is sensitive to changes resulting from dental caries treatment interventions. However, this instrument is available only in English, Chinese and Arabic languages. Therefore, this study aimed to translate and cross-culturally adapt the CARIES-QC into Brazilian Portuguese. The CARIES-QC is a dental caries-specific HRQL designed for children and adolescents aged 5 to 16 years. It contains, without differentiation according to age group applied, an initial questionnaire, containing 12 items and one global question; and a follow-up version, applied after interventions for dental caries. This second version differs from the initial version by adding a single question (item 14) that evaluates the feeling of improvement or not regarding the teeth since the first time the questionnaire was answered. Initially, discussions about conceptual and item equivalence were held by a committee of experts on the subject. Next, semantic equivalence was performed, involving the following steps: (1) translations of the CARIES-QC into Brazilian Portuguese, performed by two independent, Brazilian translators fluent in English; (2) unification of the two translations by a Committee of Experts; (3) back-translations performed independently by two native English translators fluent in Brazilian Portuguese; (4) unification of the two back-translations by a Committee of Experts; (5) evaluation of the unified version by the authors of the original instrument; (6) revision of the translations and back-translations according to the considerations of the original authors by the Committee of Experts; (7) pre-test with the application of the questionnaires to a group of 10 subjects to assess the understanding and acceptability of the instruments, and subsequent correction of the identified needs; (8) elaboration of the final instrument in Brazilian Portuguese (B-CARIES-QC). Overall, the translations and back-translations were very similar and minor changes were necessary. In the pre-test with the target population, changes were indicated and incorporated in the final version of the instrument, after approval by the original authors. Among the main changes was the standardization of the sentence structure, as well as the standardization of the response options. After all steps were completed, the Brazilian version of the CARIES-QC (B-CARIES-QC) was obtained. The translations and back-translations evaluated by the original authors and by specialists and the incorporation of suggestions from the target population allowed the construction of the B-CARIES-QC semantically equivalent to the original instrument